2010
DOI: 10.1016/j.freeradbiomed.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic vs aerobic pathways of carbonyl and oxidant stress in human lens and skin during aging and in diabetes: A comparative analysis

Abstract: The effects of anaerobic (lens) vs aerobic (skin) environment on carbonyl and oxidant stress are compared using de novo and existing data on advanced glycation and oxidation products in human crystallins and collagen. Almost all modifications increase with age. Methylglyoxal hydroimidazolones (MG-H1), carboxymethyl-lysine (CML), and carboxyethyl-lysine (CEL) are several folds higher in lens than skin, and markedly increase upon incubation of lens crystallins with 5 mM ascorbic acid. Vice-versa, fructose-lysine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 47 publications
(63 reference statements)
1
37
0
Order By: Relevance
“…Similarly, there was no reduction of MG-H1 by improved glycemic control. These data, together with the recent demonstration that only three out of 23 skin collagen specimens from diabetic donors had elevated MG-H1 levels 31 suggests that tissue-bound methylglyoxal levels are sporadically elevated in diabetic humans, although serum and LDL-bound levels clearly are elevated by diabetes 37,38 . Similarly to MG-H1, CEL was not reduced by glycemic control, although it was elevated by diabetes (Fig.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Similarly, there was no reduction of MG-H1 by improved glycemic control. These data, together with the recent demonstration that only three out of 23 skin collagen specimens from diabetic donors had elevated MG-H1 levels 31 suggests that tissue-bound methylglyoxal levels are sporadically elevated in diabetic humans, although serum and LDL-bound levels clearly are elevated by diabetes 37,38 . Similarly to MG-H1, CEL was not reduced by glycemic control, although it was elevated by diabetes (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…While considerable work remains to be performed on the full biological effects of GSPNE, its formation in diabetes is expected to be highly deleterious because it is the single major AGE and extracellular matrix (ECM) protein crosslink discovered to date 31 . First, it is expected to dramatically decrease the turnover rate of the modified ECM and contribute to basement membrane thickening in diabetes, 32 decreasing the tissue repair rate, as observed in diabetic nephropathy 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Another important function of GSH is the detoxification of the oxoaldehydes glyoxal and methylglyoxal, the latter being one of the most important sources of protein damage in aging and cataractous lenses [12], [13], [34]. For this reason we expected to find increased levels of carboxymethyl-lysine (CML), carboxyethyl-lysine (CEL) and MG-H1 hydroimidazolone.…”
Section: Discussionmentioning
confidence: 96%
“…This is in part attributed to lowered Îł-glutamyl-cysteine ligase (Gcl) activity [10] and a barrier to GSH diffusion toward the nucleus [9]. As a result ascorbic acid is increasingly oxidized throughout life leading to accelerated accumulation of crystallin-bound advanced glycation end products (AGEs) that contribute to cataractogenesis [11], [12], [13]. Concomitantly, increased protein residue oxidation is observed, as reflected by the formation of methionine sulfoxide, protein disulfides, kynurenine, and o-tyrosine from methionine, cysteine, tryptophan and phenylalanine, respectively [13], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have also demonstrated a decreased activity of the glyoxalase system and subsequently accumulation of MGO-derived AGEs in the ageing human lens, which can potentially contribute to the development of age-dependent cataracts [5, 56,57,[242][243][244][245]. Age-related endothelial dysfunction is ameliorated by an overexpression of the GLO1 enzyme, because it leads to the inhibition of MGO and subsequent inhibition of eNOS phosphorylation [246].…”
Section: Ageingmentioning
confidence: 99%